1999
DOI: 10.1111/j.1749-6632.1999.tb09531.x
|View full text |Cite
|
Sign up to set email alerts
|

Single‐Chain Antibodies in Pancreatic Cancer

Abstract: Pancreatic cancer is a therapeutic challenge for surgical and medical oncology. Development of specific molecular tracers for the diagnosis and treatment of this lethal cancer has been one of our major goals. Monoclonal antibodies (MAbs) have been successfully used as selective carriers for delivering radionuclides, toxins or cytotoxic drugs to malignant cell populations; therefore, monoclonal antibody technology has led to a significant amount of research into optimizing targeted therapy. This targeted therap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…Welinder et al [183] reported that the murine anti-Tn antibody displayed anti-tumor activity in xenograft SCID mice. Human tumor-associated glycoprotein-72 (TAG-72) is a carcinoma mucin molecule expressed in colon [184,185], breast [186], pancreatic [187], ovarian [188], lung, and gastric cancers [189]. Epitopes of TAG-72 recognized by the mAbs B72.3 and CC49 are STn and Sialyl T antigens, respectively [190192].…”
Section: Targeting the Tn Antigen In Cancermentioning
confidence: 99%
“…Welinder et al [183] reported that the murine anti-Tn antibody displayed anti-tumor activity in xenograft SCID mice. Human tumor-associated glycoprotein-72 (TAG-72) is a carcinoma mucin molecule expressed in colon [184,185], breast [186], pancreatic [187], ovarian [188], lung, and gastric cancers [189]. Epitopes of TAG-72 recognized by the mAbs B72.3 and CC49 are STn and Sialyl T antigens, respectively [190192].…”
Section: Targeting the Tn Antigen In Cancermentioning
confidence: 99%
“…Indeed these divalent scFvs revealed improved antigen affinity in vitro when compared to the monovalent scFvs. In animal models, divalent scFvs exhibited a significant improvement in tumor-targeting over monovalent species like scFv and Fab due to higher avidity and also because of an increase in size causing a longer availability of scFvs for tumor uptake [56,65,[72][73][74]. Wu et al [72] added a human Ig hinge region followed by the human CH 3 domain connected by a 10 amino acid linker (Flex minibody).…”
Section: Recombinant Antibodies: a Search For Improved Radioimmunodiamentioning
confidence: 99%
“…CC49 is among the most extensively studied MAbs for cancer therapy and reacts against tumorassociated antigen TAG-72 which is expressed by a majority of mucinous adenocarcinomas [5]. Further, we have applied the PBPK model to simulate the pharmacokinetics and biodistribution of di-and tetravalent scFv constructs of CC49 in mice.…”
Section: Introductionmentioning
confidence: 99%
“…In an effort to reduce their size and to circumvent some of the problems associated with the use of intact MAbs, immunoglobulins (IgGs) have been engineered to retain only the domains involved with antigen binding and/or mediating the effector functions of the MAb [4]. One such engineering strategy is the use of single-chain antibody fragments (scFvs) comprised of only the variable regions of the heavy and light chains of IgG, covalently connected by a flexible peptide linker [5,6]. Such fragments exhibit greater systemic clearances than intact IgG [7] and have yielded improvements in radioimmunodiagnosis and radioimmunotherapy by offering shorter imaging times and correspondingly rapid tumor penetration resulting in increased tumorto-background concentration ratios [8].…”
Section: Introductionmentioning
confidence: 99%